2020
DOI: 10.1038/s41598-020-71873-3
|View full text |Cite
|
Sign up to set email alerts
|

The number and composition of work hours for attending physicians in Taiwan

Abstract: Long work hours among physicians is a worldwide issue in the healthcare arena. Previous studies have largely focused on the work hours of resident physicians rather than those of attending physicians. The purpose of this study was to investigate total work hours and the composition of those work hours for attending physicians across different hospital settings and across different medical specialties through a nationwide survey. This included examining differences in physician workload and its composition with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…Generally, health professionals in the sub-Saharan African region have a heavy workload owed to shortages in the health workforce caused by brain drain and nursing care is the most affected. Studies show that long working hours inhibit the opportunities for recovery necessary to be healthy [ 43 ]. Our findings suggest that working for long hours has detrimental effects on nurses through fatigue, health, and pleasure deprivation which is supported by other studies [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, health professionals in the sub-Saharan African region have a heavy workload owed to shortages in the health workforce caused by brain drain and nursing care is the most affected. Studies show that long working hours inhibit the opportunities for recovery necessary to be healthy [ 43 ]. Our findings suggest that working for long hours has detrimental effects on nurses through fatigue, health, and pleasure deprivation which is supported by other studies [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that working long hours limits the opportunities for recovery necessary to be healthy and happy [ 6 ]. In addition, it has a detrimental effect on SWB through individuals’ fatigue, health deprivation, and time pressure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as a risk factor for fatigue, over-pressure, negative emotions, and continual long-term work could hurt the work itself. In the medical field, working long hours is a predictive factor of reduced productivity, increasing medical errors, high absenteeism, abuse of sickness absence, and even turnover intention [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a growing aging population with chronic and age-related diseases, along with subsequently ever increasing health care demands worldwide ( 1 ), especially in China ( 2 ), alarming increasing trends in physician workload have attracted much attention from health care providers, researchers and decision makers in recent years, owing to lack of a proportional growth in the number of physicians ( 3 5 ). Increased physician workload is associated with their worse occupational health ( 6 , 7 ), inferior quality of medical care and even patient harm ( 5 , 7 9 ). Healthcare organizations may also experience adverse effects such as low productivity, increased cost ( 10 ), and increased use of sick leave and turnover rates among physicians ( 9 ).…”
Section: Introductionmentioning
confidence: 99%